Cookies are magic : classic cookies, brownies, bars, and more - Heatter, Maida (Voracious/Little, Brown and Company, 2020)
"Maida knew that cookies are the key to happiness, and she always kept them nearby: a fudgy, minty Palm Beach Brownie in her purse, neatly wrapped in cellophane, a batch of Absolutely-the-Positively-Best Chocolate Chip Cookies in the freezer, or a box of delicate brandy snaps ready for an elegant gift. Now, Cookies Are Magic collects nearly 100 of Maida's very best recipes from her "legendary" (New York Times) 50-year career-her crispiest, crunchiest, and most ooey-gooey cookies, bars, and more. Developed for foolproof baking by anyone, each recipe is written with Maida's warm but no-nonsense instructions and carries her guarantee that it will work perfectly every time. Filled with classic sugar cookies, tart lemon bars, cookie kisses, and chocolate and peanut butter ripples, this is the only cookie book you will ever need."--Amazon.com.